Solid oxide fuel cell electrolyte with rotary honeycomb structure as well as preparation and application of solid oxide fuel cell electrolyte
The preparation of solid oxide fuel cell electrolytes with rotating honeycomb structures through DLP photocuring 3D printing technology has solved the problems of complex process and high cost when preparing complex structure electrolytes in the prior art, and achieved efficient and low-cost electrochemical performance improvement.
Patent Information
- Application Number
- CN202411662259.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, when preparing solid oxide fuel cell electrolytes, the process is complex and the flexibility is poor, resulting in low working efficiency and high cost, making it difficult to effectively prepare complex structures.
DLP photocuring 3D printing technology is used to prepare battery electrolytes with rotary honeycomb structures, and the surface area and volume ratio of the electrolyte is increased through the rotary honeycomb structure and reduced production costs.
It effectively improves the electrochemical performance of solid oxide fuel cells, reduces production costs, and promotes the development of mobile portable applications.
Smart Images

Figure CN119650778A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid oxide fuel cells, and in particular to a solid oxide fuel cell electrolyte with a rotating honeycomb structure and the preparation and application thereof. Background Art
[0002] Since the 20th century, the energy consumption and environmental problems caused by the inefficient use of traditional fossil energy have become increasingly severe. People are forced to develop new low-pollution and high-efficiency power generation technologies. Solid oxide fuel cell (SOFC), as a new generation of fuel cells, is an energy conversion device that directly converts the chemical energy in the fuel into electrical energy and thermal energy. The most intuitive feature of its solid oxide fuel cell is its high efficiency and environmental protection. It is the fuel cell with the highest energy conversion efficiency.
[0003] Solid oxide fuel cells (SOFCs) are electrochemical devices that can directly convert the chemical energy of a chemical reaction into electrical current while eliminating the actual combustion step and are therefore not limited by the Carnot cycle. As can be seen, SOFCs have some unique advantages, such as fuel flexibility, and due to their high operating temperature and tolerance to common fossil fuel impurities, they can use not only hydrogen but also hydrocarbons and even biochar as fuels. In SOFCs, the electrochemical conversion process of converting the chemical energy of a fuel into electrical energy has been considered one of the technologies that can revolutionize the power generation industry. Small size and high density solid oxide fuel cells are the only way for fuel cells to develop into portable applications.
[0004] SOFCs are sandwich structures consisting of a porous anode and cathode separated by a dense electrolyte layer. The dense electrolyte is usually ceramic, which is not only a barrier between the fuel gas and the air, but also an ion transport medium. Oxygen is adsorbed at the cathode and dissociated into O 2- , O 2- It passes through the electrolyte to the anode and combines with the protons produced by HOR in the anode reaction zone to generate H2O. The electrolyte-supported solid oxide fuel cell has a strong structure and good mechanical stability.
[0005] The processes commonly used to prepare electrolyte supports at present include various processes such as casting, stamping, screen printing, lamination and stacking. These molding preparation processes have high requirements for slurry, and the process flow is complex and inflexible, resulting in low work efficiency and high cost, making it difficult to effectively prepare solid electrolytes with complex structures.
[0006] Therefore, it is very important to provide a technical solution that can solve the above problems. Summary of the invention
[0007] In order to solve the above problems, the purpose of the present invention is to provide a solid oxide fuel cell electrolyte with a rotating honeycomb structure and its preparation and application. The present invention increases the specific surface area by rotating the honeycomb structure, and because the sum of the three normal stresses is zero during rotation, the volume remains unchanged, which effectively improves the surface area to volume ratio of the battery electrolyte, reduces production costs, promotes the development of mobile and portable application fields, and solves the shortcomings of the prior art. The present invention adopts DLP light-curing 3D printing technology to prepare a battery electrolyte with a rotating honeycomb structure with a high specific surface area. In combination with the above, the method provided in the present application can effectively improve the electrochemical performance of solid oxide fuel cells.
[0008] In recent years, 3D printing has promoted the development of the manufacturing industry with its unique advantages, especially photocuring 3D printing, which has high precision, fast speed, and can prepare any complex shape without machining and molds. It has the significant advantages of saving materials and reducing manufacturing costs, which can provide a new idea for the preparation of SOFCs electrolyte supports and may realize the integrated production of SOFCs. However, the rotating honeycomb structure increases the three boundaries by rotating the electrolyte body. When the rotation angle is too small, the increase in the three-phase interface area will be too small, and the improvement of electrochemical performance will not be obvious; when the rotation angle is too large, it will cause over-support phenomenon, and ultimately cannot be printed.
[0009] The purpose of the present invention can be achieved by the following technical solutions:
[0010] The first object of the present invention is to provide a solid oxide fuel cell electrolyte having a rotating honeycomb structure, wherein the solid oxide fuel cell electrolyte having a rotating honeycomb structure is obtained by rotating the solid oxide fuel cell electrolyte having a honeycomb structure along the x, y, and z directions as the origin;
[0011] The rotation angle is 15 to 90 degrees.
[0012] In the present invention, the unrotated honeycomb structure has a volume (1mm 3 ) surface area is 6.04mm 2 ;
[0013] When rotated 15°, each volume (1mm 3 ) surface area is 6.2mm 2 ;
[0014] When rotated 30°, each volume (1mm 3 ) surface area is 6.5mm 2 ;
[0015] When rotated 45°, each volume (1mm 3 ) surface area is 6.8mm2 ;
[0016] When rotated 60°, each volume (1mm 3 ) surface area is 6.98mm 2 ;
[0017] When rotated 90°, each volume (1mm 3 ) surface area is 7.21mm 2 ;
[0018] When rotated 180°, a solid oxide fuel cell electrolyte with a rotated honeycomb structure cannot be obtained.
[0019] In the present invention, when the rotation angle is between 15° and 90°, since the volume change rate during rotation is proportional to the sum of the positive stresses in the x, y, and z directions, and the sum of the three positive stresses (x-direction positive stress, y-direction positive stress, and z-direction positive stress) is zero, the volume remains unchanged, thereby effectively increasing the surface area of the battery electrolyte.
[0020] The second object of the present invention is to provide a method for preparing a solid oxide fuel cell electrolyte having a rotating honeycomb structure, comprising the following steps:
[0021] (S1) curing and printing a photosensitive resin slurry containing zirconium oxide using DLP light-curing printer parameters to obtain a solid oxide fuel cell electrolyte green body with a rotating honeycomb structure;
[0022] (S2) subjecting the solid oxide fuel cell electrolyte green body with a rotating honeycomb structure prepared in step (S1) to a binder removal and sintering process to obtain a solid oxide fuel cell electrolyte with a rotating honeycomb structure.
[0023] In one embodiment of the present invention, in step (S1), the preparation of the photosensitive resin slurry containing zirconium oxide comprises the following steps:
[0024] (S11) mixing the photosensitive resin and the dispersant to obtain a first mixed solution;
[0025] (S12) mixing the ceramic powder containing zirconium oxide with the first mixed solution, and then adding a photoinitiator and a defoaming agent to obtain a second mixed solution;
[0026] (S13) mixing the grinding aid with the second mixed solution, and ball milling to obtain a photosensitive resin slurry containing zirconium oxide;
[0027] In one embodiment of the present invention, in step (S11), the photosensitive resin is selected from one or more of polyethylene glycol, polyvinyl alcohol, 1,6-hexanediol diacrylate, 2-hydroxyethyl acrylate or trihydroxymethylpropane triacrylate;
[0028] The dispersant is selected from one or both of CPD-01 and CPD-02;
[0029] In step (S12), the ceramic powder containing zirconium oxide is 8 mol yttria-stabilized zirconium oxide ceramic powder, and its average particle size is 200-300 nm;
[0030] The photoinitiator is selected from one of TPO-01 and TPO-02;
[0031] The defoamer is SN-348;
[0032] In step (S13), the grinding aid is a zirconia ball with a diameter of 3 mm to 5 mm;
[0033] Preferably, the grinding aid is a mixture of three types of zirconium oxide balls with diameters of 3 mm, 4 mm and 5 mm respectively.
[0034] In one embodiment of the present invention, the volume ratio of the photosensitive resin, the dispersant, the ceramic powder containing zirconium oxide and the photoinitiator is 20-55%: 2-6%: 40-60%: 2-6%.
[0035] In one embodiment of the present invention, during the ball milling process, the rotation speed is 100 to 300 r / min and the time is 9 to 10 hours.
[0036] In one embodiment of the present invention, in step (S1), during the curing printing process, the parameters are as follows:
[0037] The LED light source equipped in the printer has a wavelength of 395nm, a printing layer thickness of 0.05 to 0.1mm, and a light intensity of 9 to 20mW / cm 2 , bottom exposure layers 0 to 9999, bottom exposure time 1 to 20s, exposure time for each layer 1 to 20s, waiting time after each layer exposure is 1 to 3s.
[0038] In one embodiment of the present invention, in step (S2), during the debinding sintering process, the parameters are as follows:
[0039] The first stage: 0-300℃, heating rate of 1-3℃ / min, heating to 300℃ and keeping warm for 3-4h;
[0040] The second stage: 300-600℃, heating rate is 2-4℃ / min, heating to 600℃ and keeping warm for 6-7h;
[0041] The third stage: 600-1500℃, heating rate of 5-7℃ / min, heating to 1500℃ and keeping warm for 1.5-2h;
[0042] Stage 4: Natural cooling to room temperature.
[0043] The third object of the present invention is to provide an application of a solid oxide fuel cell electrolyte having a rotating honeycomb structure in the preparation of a solid oxide fuel cell.
[0044] A fourth object of the present invention is to provide a method for preparing a solid oxide fuel cell, comprising the following steps:
[0045] (A1) mixing a nickel oxide solvent and a pine alcohol solvent to obtain an anode slurry;
[0046] The LSC is mixed with pinene alcohol solvent to obtain cathode slurry;
[0047] (A2) injecting the anode slurry prepared in step (A1) into one side of the electrolyte of the solid oxide fuel cell having a honeycomb structure, and performing a first sintering treatment after a first drying;
[0048] Then, the cathode slurry prepared in step (A1) is injected into the other side of the electrolyte of the solid oxide fuel cell having a honeycomb structure, and after a second drying, a second sintering treatment is performed to obtain a solid oxide fuel cell.
[0049] In one embodiment of the present invention, in step (A1), the volume ratio of the nickel oxide solvent to the pineneol solvent is 4:6;
[0050] The solid content of the cathode slurry is 30% to 45%;
[0051] In step (A2), during the first drying process, the temperature is 100° C., and during the first sintering process, the temperature is 1150-1400° C.;
[0052] During the second drying process, the temperature is 100°C, and during the second sintering process, the temperature is 850-1150°C.
[0053] The fifth object of the present invention is to provide a solid oxide fuel cell prepared by the above method.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] (1) The present invention obtains a solid oxide fuel cell electrolyte with a honeycomb structure through modeling and calculation. Since the sum of the three normal stresses is zero during rotation, the volume remains unchanged, which effectively improves the surface area-to-volume ratio of the battery electrolyte, thereby increasing the active area for reacting with the reaction gas; reducing the production cost, promoting the development of mobile and portable application fields, and solving the shortcomings of the prior art.
[0056] (2) The present invention uses high-precision photocuring 3D printing technology for printing and molding to obtain an electrolyte green body with uniform layer thickness and controllable macroscopic morphology.
[0057] (3) The present invention provides favorable conditions for the development of electrolyte-supported SOFCs, provides new ideas for the preparation of complex-shaped electrolytes for small-volume SOFCs, and lays a foundation for the integrated production of SOFCs. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 A structural model diagram of a solid oxide fuel cell having a rotating honeycomb structure;
[0059] Numbers in the figure: 1, cubic column model; 2, first honeycomb groove; 3, first plane;
[0060] Figure 2 A top view of a solid oxide fuel cell having a rotating honeycomb structure;
[0061] Figure 3 This is a front view of a solid oxide fuel cell with a rotating honeycomb structure. DETAILED DESCRIPTION
[0062] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0063] In the following examples, unless otherwise specified, all reagents used are commercially available reagents, and all detection means and methods used are conventional detection means and methods in the art.
[0064] Example 1
[0065] This embodiment provides a method for preparing a solid oxide fuel cell electrolyte having a rotating honeycomb structure, comprising the following steps:
[0066] (S1) firstly, 30 g of polyethylene glycol, 30 g of polyvinyl alcohol, 90 g of 1,6-hexanediol diacrylate, 75 g of 2-hydroxyethyl acrylate, and 25 g of trihydroxymethylpropane triacrylate were mixed to obtain a photosensitive resin solution;
[0067] (S2) adding 98.637 g of dispersant CPD-01 to the photosensitive resin solution prepared in step (S1), and mixing thoroughly to obtain a first mixed solution;
[0068] (S3) weighing 1537.2 g of 8YSZ (8 mol yttria-stabilized zirconia) ceramic powder with an average particle size of 300 nm on a balance, adding it to the first mixed solution prepared in step (S2), mixing well, and then adding 6.42 g of a photoinitiator (TPO-01) and 3.15 g of a defoaming agent (SN-348) to obtain a second mixed solution;
[0069] (S4) using 500 g of zirconia spheres with diameters of 3 mm, 4 mm, and 5 mm as grinding aids, the second mixed solution was ball-milled at a speed of 300 r / min (10 hours) to obtain a photosensitive resin slurry containing zirconium oxide;
[0070] (S5) pouring the photosensitive resin slurry prepared in step (S4) into a material tank of a DLP light-curing printer;
[0071] (S6) Using the 3D modeling software Magics to create a rotated honeycomb structure, create a rotated honeycomb structure of the same size, and rotate the rotated honeycomb model by 0°, 15°, 30°, 45°, 60°, and 90°, as shown in Figure 1 As shown, the created honeycomb model structure is converted into an STL file, sliced, and the sliced file is uploaded to the printer;
[0072] The dimensions of the rotated honeycomb model when rotated 0° are as follows:
[0073] A cubic column model 1 having a length (x direction) of 18.3 mm, a width (y direction) of 18.3 mm, and a height (z direction) of 10 mm, wherein a plurality of first honeycomb grooves 2 (length 1.67 mm, width 1.67 mm, depth 9.6 mm) are alternately arranged on the top surface of the cubic column model 1, and a first plane 3 (length 2.27 mm, width 2.27 mm) exists between adjacent first honeycomb grooves 2; a plurality of second honeycomb grooves (length 1.67 mm, width 1.67 mm, depth 9.6 mm) are alternately arranged on the bottom surface of the cubic column model 1 m, width 1.67mm, depth 9.6mm), there is a second plane (length 2.27mm, width 2.27mm) between adjacent second honeycomb grooves; wherein, the first honeycomb grooves 2 and the second honeycomb grooves are alternately arranged, the center point of any second honeycomb groove and the center point of the corresponding first plane 3 (corresponding along the z direction) are located on the same z-axis, and the center point of any first honeycomb groove 2 and the center point of the corresponding second plane (corresponding along the z direction) are located on the same z-axis.
[0074] (S7) The specific parameters of the printer are adjusted as follows: the wavelength of the LED light source on the printer is 395nm, the printing layer thickness is 0.05mm, and the light intensity is 20mW / cm 2 , the first three layers of bottom exposure, bottom exposure time 16s, the exposure time of each layer after the third layer is 15s, and the waiting time after each layer exposure is 1s,
[0075] After all settings are completed, the DLP light-curing 3D printer starts to cure and print layer by layer;
[0076] (S8) removing the printed solid oxide fuel cell electrolyte green body with a rotating honeycomb structure using a scraper and cleaning it with alcohol;
[0077] (S9) placing the cleaned solid oxide fuel cell electrolyte green body with rotating honeycomb structure into a muffle furnace for debinding and sintering, wherein the debinding and sintering parameters are as follows:
[0078] The first stage: 0-300℃, heating rate is 1℃ / min, heating to 300℃ and keeping warm for 3.5h;
[0079] The second stage: 300-600℃, heating rate is 2℃ / min, heating to 600℃ and keeping warm for 7h;
[0080] The third stage: 600-1500℃, heating rate of 5℃ / min, heating to 1500℃ and keeping warm for 2h;
[0081] Stage 4: Natural cooling to room temperature.
[0082] A solid oxide fuel cell electrolyte having a rotating honeycomb structure (such as Figure 2 and Figure 3 shown), Figure 2 and Figure 3 In the figure, from left to right are actual pictures of a solid oxide fuel cell electrolyte with a rotated honeycomb structure, which are not rotated (rotated 0°), rotated 15°, rotated 30°, rotated 45°, rotated 60°, and rotated 90°.
[0083] Among them, the unrotated honeycomb structure has a volume (1mm 3 ) surface area is 6.04mm 2 ;
[0084] When rotated 15°, each volume (1mm 3 ) surface area is 6.2mm 2 ;
[0085] When rotated 30°, each volume (1mm 3 ) surface area is 6.5mm 2 ;
[0086] When rotated 45°, each volume (1mm 3 ) surface area is 6.8mm 2 ;
[0087] When rotated 60°, each volume (1mm 3 ) surface area is 6.98mm 2 ;
[0088] When rotated 90°, each volume (1mm 3 ) surface area is 7.21mm 2 .
[0089] Example 2
[0090] This embodiment provides a method for preparing a solid oxide fuel cell, comprising the following steps:
[0091] (A1) Preparation of anode slurry: Mix nickel oxide solvent and pine alcohol solvent in a ratio of 4:6 to prepare a liquid slurry with high fluidity. Inject the prepared anode slurry into one side of the electrolyte of a rotating honeycomb structure solid oxide fuel cell with a high specific surface area (one side of the first honeycomb groove and the first plane) by injection, dry at 100 degrees Celsius, and then sinter at 1350 degrees Celsius;
[0092] (A2) Preparation of cathode slurry: Sr-doped La 0.6 Sr 0.4 CoO3 (LSC) cathode material is semi-solid and mixed with pinepine solvent to prepare a cathode slurry with a solid content of 30%; the obtained cathode slurry is injected into the other side (one side of the second honeycomb groove and the second plane) of a rotating honeycomb structure solid oxide fuel cell electrolyte with a high specific surface area, dried at 100 degrees Celsius and then sintered at 1100 degrees Celsius to obtain a solid oxide fuel cell.
[0093] The prepared solid oxide fuel cell sample was placed in the SOFC test equipment, and a stable voltage of 1.08V was obtained at 800°C, which is close to the theoretical value; the power density was calculated as follows:
[0094] Among them, the power density of the unrotated honeycomb structure is 212mW / cm 2 ;
[0095] When rotated 15°, the power density is 232mW / cm 2 ;
[0096] When rotated 30°, the power density is 251mW / cm 2 ;
[0097] When rotated 45°, the power density is 267mW / cm 2 ;
[0098] When rotated 60°, the power density is 286mW / cm 2 ;
[0099] When rotated 90°, the power density is 312mW / cm 2 .
[0100] Example 3
[0101] This embodiment provides a method for preparing a solid oxide fuel cell electrolyte having a rotating honeycomb structure, which is the same as that of Embodiment 1 except for the following conditions.
[0102] (S6) using the 3D modeling software Magics to create a rotated honeycomb structure (the size of the rotated honeycomb model rotated 0° is the same as that in Example 1), creating a rotated honeycomb structure of the same size, rotating the rotated honeycomb model 90°, converting the created honeycomb model structure into an stl file, slicing it, and uploading the sliced file to a printer;
[0103] (S7) The specific parameters of the printer are adjusted as follows: the wavelength of the LED light source on the printer is 400nm, the printing layer thickness is 0.05mm, and the light intensity is 15mW / cm 2 , 3 layers before bottom exposure, bottom exposure time 20s, exposure time after 3 layers 18s, waiting time 2s after each layer exposure, after all settings, the DLP light-curing 3D printer starts to cure and print layer by layer.
[0104] (S9) placing the cleaned solid oxide fuel cell electrolyte green body with rotating honeycomb structure into a muffle furnace for debinding and sintering, wherein the debinding and sintering parameters are as follows:
[0105] The first stage: 0-300℃, heating rate of 1-3℃ / min, heating to 300℃ and keeping warm for 3h;
[0106] The second stage: 300-600℃, heating rate of 2-4℃ / min, heating to 600℃ and keeping warm for 6h;
[0107] The third stage: 600-1500℃, heating rate of 5-7℃ / min, heating to 1500℃ and keeping warm for 2h;
[0108] Stage 4: Natural cooling to room temperature.
[0109] A solid oxide fuel cell electrolyte with a rotating honeycomb structure is obtained.
[0110] Example 4
[0111] This embodiment provides a method for preparing a solid oxide fuel cell, comprising the following steps:
[0112] (A1) Preparation of anode slurry: Mix nickel oxide solvent and pine alcohol solvent in a ratio of 5:5 to prepare a liquid slurry with high fluidity. Inject the prepared anode slurry into one side of a rotating honeycomb structure solid oxide fuel cell electrolyte with a high specific surface area (prepared in Example 3) by injection, dry at 100 degrees Celsius, and then sinter at 1200 degrees Celsius;
[0113] (A2) Preparation of cathode slurry: Sr-doped La 0.6 Sr 0.4CoO3 (LSC) cathode material is semi-solid and mixed with pinepine solvent to prepare a cathode slurry with a solid content of 40%; the obtained cathode slurry is injected into the other side of a rotating honeycomb structure solid oxide fuel cell electrolyte with a high specific surface area, dried at 100 degrees Celsius and sintered at 900 degrees Celsius to obtain a solid oxide fuel cell.
[0114] The prepared solid oxide fuel cell sample was placed in the SOFC test equipment, and a stable voltage of 1.01V was obtained at 750°C, which is close to the theoretical value; the calculated power density is 259mW / cm 2 .
[0115] Example 5
[0116] This embodiment provides a method for preparing a solid oxide fuel cell electrolyte having a rotating honeycomb structure, which is the same as that of Embodiment 1 except for the following conditions.
[0117] (S1) firstly, 30 g of polyethylene glycol, 30 g of polyvinyl alcohol, 75 g of 1,6-hexanediol diacrylate, 25 g of 2-hydroxyethyl acrylate, and 90 g of trihydroxymethylpropane triacrylate were mixed to obtain a photosensitive resin solution;
[0118] (S2) adding 105 g of dispersant CPD-02 to the photosensitive resin solution prepared in step (S1), and mixing thoroughly to obtain a first mixed solution;
[0119] (S3) adding 1537.2 g of 8YSZ (8 mol yttria-stabilized zirconia) ceramic powder having an average particle size of 300 nm to the first mixed solution prepared in step (S2), mixing well, and then adding 5 g of a photoinitiator (TPO-02) and 3.20 g of a defoamer (SN-348) to obtain a second mixed solution;
[0120] (S6) using the 3D modeling software Magics to create a rotated honeycomb structure (the size of the rotated honeycomb model rotated 0° is the same as that in Example 1), creating a rotated honeycomb structure of the same size, rotating the rotated honeycomb model 90°, converting the created honeycomb model structure into an stl file, slicing it, and uploading the sliced file to a printer;
[0121] (S7) The specific parameters of the printer are adjusted as follows: the wavelength of the LED light source on the printer is 400nm, the printing layer thickness is 0.05mm, and the light intensity is 15mW / cm 2 , the number of bottom exposure layers is 3 layers, the bottom exposure time is 18s, the exposure time after 3 layers is 16s, and the waiting time after each layer is exposed is 2s. After all the settings are made, the DLP light-curing 3D printer starts to cure and print layer by layer.
[0122] (S9) placing the cleaned solid oxide fuel cell electrolyte green body with rotating honeycomb structure into a muffle furnace for debinding and sintering, wherein the debinding and sintering parameters are as follows:
[0123] The first stage: 0-300℃, heating rate is 2℃ / min, heating to 300℃ and keeping warm for 3h;
[0124] The second stage: 300-600℃, heating rate is 3℃ / min, heating to 600℃ and keeping warm for 6h;
[0125] The third stage: 600-1500℃, heating rate is 6℃ / min, heating to 1500℃ and keeping warm for 1.5h;
[0126] Stage 4: Natural cooling to room temperature.
[0127] A solid oxide fuel cell electrolyte with a rotating honeycomb structure is obtained.
[0128] Example 6
[0129] This embodiment provides a method for preparing a solid oxide fuel cell, comprising the following steps:
[0130] (A1) Preparation of anode slurry: Mix nickel oxide solvent and pine alcohol solvent in a ratio of 5:5 to prepare a liquid slurry with high fluidity. Inject the prepared anode slurry into one side of a rotating honeycomb structure solid oxide fuel cell electrolyte with a high specific surface area (prepared in Example 5) by injection, dry at 100 degrees Celsius, and then sinter at 1400 degrees Celsius;
[0131] (A2) Preparation of cathode slurry: Sr-doped La 1-x Sr x CoO3 (LSC) cathode material is semi-solid and mixed with pinepine solvent to prepare a cathode slurry with a solid content of 45%; the obtained cathode slurry is injected into the other side of a rotating honeycomb structure solid oxide fuel cell electrolyte with a high specific surface area, dried at 100 degrees Celsius and sintered at 1000 degrees Celsius to obtain a solid oxide fuel cell.
[0132] The prepared solid oxide fuel cell sample was placed in the SOFC test equipment, and a stable voltage of 1.01V was obtained at 750°C, which is close to the theoretical value; its power density is 252mW / cm 2 .
[0133] Comparative Example 1
[0134] (S1) firstly, 30 g of polyethylene glycol, 30 g of polyvinyl alcohol, 90 g of 1,6-hexanediol diacrylate, 75 g of 2-hydroxyethyl acrylate, and 25 g of trihydroxymethylpropane triacrylate were mixed to obtain a photosensitive resin solution;
[0135] (S2) adding 98.637 g of dispersant CPD-01 to the photosensitive resin solution prepared in step (S1), and mixing thoroughly to obtain a first mixed solution;
[0136] (S3) weighing 1537.2 g of 8YSZ (8 mol yttria-stabilized zirconia) ceramic powder with an average particle size of 300 nm on a balance, adding it to the first mixed solution prepared in step (S2), mixing well, and then adding 6.42 g of a photoinitiator (TPO-01) and 3.15 g of a defoaming agent (SN-348) to obtain a second mixed solution;
[0137] (S4) using 500 g of zirconia spheres with diameters of 3 mm, 4 mm, and 5 mm as grinding aids, the second mixed solution was ball-milled at a speed of 300 r / min (10 hours) to obtain a photosensitive resin slurry containing zirconium oxide;
[0138] (S5) pouring the photosensitive resin slurry prepared in step (S4) into a material tank of a DLP light-curing printer;
[0139] (S6) using the 3D modeling software Magics to create a rotated honeycomb structure (the size of the rotated honeycomb model rotated 0° is the same as that in Example 1), creating a rotated honeycomb structure of the same size, rotating the rotated honeycomb model by 10°, converting the created honeycomb model structure into an stl file, slicing it, and uploading the sliced file to a printer;
[0140] (S7) The specific parameters of the printer are adjusted as follows: the wavelength of the LED light source on the printer is 395nm, the printing layer thickness is 0.05mm, and the light intensity is 20mW / cm 2 , the first 3 layers of bottom exposure, the bottom exposure time is 16s, the exposure after 3 layers is 15s, and the waiting time after each layer exposure is 1s,
[0141] After all settings are completed, the DLP light-curing 3D printer starts to cure and print layer by layer;
[0142] (S8) removing the printed solid oxide fuel cell electrolyte green body with a rotating honeycomb structure using a scraper and cleaning it with alcohol;
[0143] (S9) placing the cleaned solid oxide fuel cell electrolyte green body with rotating honeycomb structure into a muffle furnace for debinding and sintering, wherein the debinding and sintering parameters are as follows:
[0144] The first stage: 0-300℃, heating rate is 1℃ / min, heating to 300℃ and keeping warm for 3.5h;
[0145] The second stage: 300-600℃, heating rate is 2℃ / min, heating to 600℃ and keeping warm for 7h;
[0146] The third stage: 600-1500℃, heating rate of 5℃ / min, heating to 1500℃ and keeping warm for 2h;
[0147] Stage 4: Natural cooling to room temperature.
[0148] The results show that the power density of the honeycomb structure rotated 10° is 220mW / cm due to the small rotation angle. 2 (Using the electrode preparation process in Example 2), only 212 mW / cm 2 , increased by 8mW / cm 2 , if the improvement is not obvious, it will not be adopted.
[0149] Comparative Example 2
[0150] Compared with Example 1, this embodiment is the same as Example 1 except for the following conditions:
[0151] (S1) firstly, 30 g of polyethylene glycol, 30 g of polyvinyl alcohol, 90 g of 1,6-hexanediol diacrylate, 75 g of 2-hydroxyethyl acrylate, and 25 g of trihydroxymethylpropane triacrylate were mixed to obtain a photosensitive resin solution;
[0152] (S2) adding 98.637 g of dispersant CPD-01 to the photosensitive resin solution prepared in step (S1), and mixing thoroughly to obtain a first mixed solution;
[0153] (S3) weighing 1537.2 g of 8YSZ (8 mol yttria-stabilized zirconia) ceramic powder with an average particle size of 300 nm on a balance, adding it to the first mixed solution prepared in step (S2), mixing well, and then adding 6.42 g of a photoinitiator (TPO-01) and 3.15 g of a defoaming agent (SN-348) to obtain a second mixed solution;
[0154] (S4) using 500 g of zirconia spheres with diameters of 3 mm, 4 mm, and 5 mm as grinding aids, the second mixed solution was ball-milled at a speed of 300 r / min (10 hours) to obtain a photosensitive resin slurry containing zirconium oxide;
[0155] (S5) pouring the photosensitive resin slurry prepared in step (S4) into a material tank of a DLP light-curing printer;
[0156] (S6) using the 3D modeling software Magics to create a rotated honeycomb structure (the size of the rotated honeycomb model rotated 0° is the same as that in Example 1), creating a rotated honeycomb structure of the same size, rotating the rotated honeycomb model 180°, converting the created honeycomb model structure into an stl file, slicing it, and uploading the sliced file to a printer;
[0157] (S7) The specific parameters of the printer are adjusted as follows: the wavelength of the LED light source on the printer is 395nm, the printing layer thickness is 0.05mm, and the light intensity is 20mW / cm 2 , the first 3 layers of bottom exposure, the bottom exposure time is 16s, the exposure time after 3 layers is 15s, and the waiting time after each layer exposure is 1s;
[0158] After all settings are completed, the DLP light-curing 3D printer starts to cure and print layer by layer.
[0159] It was found that due to the large rotation angle, over-support occurred and printing was impossible.
[0160] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the explanation of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A solid oxide fuel cell electrolyte having a rotating honeycomb structure, characterized in that: The solid oxide fuel cell electrolyte with a rotating honeycomb structure is obtained by rotating the solid oxide fuel cell electrolyte with a honeycomb structure along the x, y and z directions as the origin; The rotation angle is 15 to 90 degrees.
2. A method for preparing a solid oxide fuel cell electrolyte having a rotating honeycomb structure as claimed in claim 1, characterized in that: The following steps are involved: (S1) curing and printing a photosensitive resin slurry containing zirconium oxide using DLP light-curing printer parameters to obtain a solid oxide fuel cell electrolyte green body with a rotating honeycomb structure; (S2) subjecting the solid oxide fuel cell electrolyte green body with a rotating honeycomb structure prepared in step (S1) to a binder removal and sintering process to obtain a solid oxide fuel cell electrolyte with a rotating honeycomb structure.
3. The method for preparing a solid oxide fuel cell electrolyte having a rotating honeycomb structure according to claim 2, characterized in that: In step (S1), the preparation of the photosensitive resin slurry containing zirconium oxide comprises the following steps: (S11) mixing the photosensitive resin and the dispersant to obtain a first mixed solution; (S12) mixing the ceramic powder containing zirconium oxide with the first mixed solution, and then adding a photoinitiator and a defoaming agent to obtain a second mixed solution; (S13) The grinding aid is mixed with the second mixed solution, and ball milling is performed to obtain a photosensitive resin slurry containing zirconium oxide.
4. The method for preparing a solid oxide fuel cell electrolyte having a rotating honeycomb structure according to claim 3, characterized in that: In step (S11), the photosensitive resin is selected from one or more of polyethylene glycol, polyvinyl alcohol, 1,6-hexanediol diacrylate, 2-hydroxyethyl acrylate or trihydroxymethylpropane triacrylate; The dispersant is selected from one or both of CPD-01 and CPD-02; In step (S12), the ceramic powder containing zirconium oxide is 8 mol yttria-stabilized zirconium oxide ceramic powder, and its average particle size is 200-300 nm; The photoinitiator is selected from one of TPO-01 and TPO-02; The defoamer is SN-348; In step (S13), the grinding aid is a zirconia ball with a diameter of 3 mm to 5 mm.
5. The method for preparing a solid oxide fuel cell electrolyte having a rotating honeycomb structure according to claim 3, characterized in that: The volume ratio of the photosensitive resin, the dispersant, the ceramic powder containing zirconium oxide and the photoinitiator is 20-55%: 2-6%: 40-60%: 2-6%.
6. The method for preparing a solid oxide fuel cell electrolyte having a rotating honeycomb structure according to claim 2, characterized in that: In step (S1), during the curing printing process, the parameters are as follows: The LED light source equipped in the printer has a wavelength of 395nm, a printing layer thickness of 0.05 to 0.1mm, and a light intensity of 9 to 20mW / cm 2 , bottom exposure layers 0 to 9999, bottom exposure time 1 to 20s, exposure time for each layer 1 to 20s, waiting time after each layer exposure is 1 to 3s.
7. The method for preparing a solid oxide fuel cell electrolyte having a rotating honeycomb structure according to claim 2, characterized in that: In step (S2), during the debinding sintering process, the parameters are as follows: The first stage: 0-300℃, heating rate is 1-3℃ / min, heating to 300℃ and keeping warm for 3-4h; The second stage: 300-600℃, heating rate is 2-4℃ / min, heating to 600℃ and keeping warm for 6-7h; The third stage: 600-1500℃, heating rate of 5-7℃ / min, heating to 1500℃ and keeping warm for 1.5-2h; Stage 4: Natural cooling to room temperature.
8. Use of the solid oxide fuel cell electrolyte with a rotating honeycomb structure as claimed in claim 1 in the preparation of a solid oxide fuel cell.
9. A method for preparing a solid oxide fuel cell, characterized in that: The following steps are involved: (A1) mixing a nickel oxide solvent and a pine alcohol solvent to obtain an anode slurry; The LSC is mixed with pinene alcohol solvent to obtain cathode slurry; (A2) injecting the anode slurry prepared in step (A1) into one side of the electrolyte of the honeycomb structured solid oxide fuel cell as claimed in claim 1, and performing a first sintering treatment after a first drying; Then, the cathode slurry prepared in step (A1) is injected into the other side of the electrolyte of the solid oxide fuel cell having a honeycomb structure, and after a second drying, a second sintering treatment is performed to obtain a solid oxide fuel cell.
10. A solid oxide fuel cell, characterized in that: Prepared by the method according to claim 9.